72.2: Development and Analysis of Technical Challenges in the World's Largest (110‐in.) Curved LCD. Issue 1 (June 2015) - Hsiao, Ken; Tang, Guofu; Yu, Gang; Zhang, Zuwei; Xu, Xiaojie; Zhang, Pangling; Lv, Chengling; Lien, Alan
Abstract : In this paper, we utilize simulation to estimate the shift value in the panel. Topology optimization is applied to improve the design of aluminum extrusion and lighten the weight of the product. Moreover, optical optimization of LED with lens is carried out to diminish the thickness of the curved display.